Youth phenomenon leaves agricultural sector in max weber social action perspective - Akbar, Ayyadana; Abdullah, Suparman; Muhammad, Rahmat (Institute of Computer Science (IOCS), 2023)
The increasing population has an impact on the growing need for food. The decrease in young farmers indicates that farmer regeneration is not going well. This situation is not favourable for the government's plan to make Indonesia the world's food granary in 2045 because it can reduce the number of domestic agricultural production so that dependence on food imports will continue to occur. This study aims to see the motives and goals of youth leaving the farm sector as a social phenomenon from the perspective of Max Weber's social action theory so that it can be an input for accelerating current and future government policies. Using qualitative research methods with a literature review approach, it was found that based on motives and goals, the youth left the agricultural sector based on instrumental rational actions and valued reasonable measures. There are no motives and goals that lead to traditional and practical actions.